A statistical study of synoptic systems causing significant Rainfall over Tamil Nadu during southwest monsoon Season - MANIKIAM, B; SRIDHARAN, DS (MAUSAM, 1988)
A statistical analysis of the five-year data (1975-79) has been carried out to study the occurrence of various synoptic systems which cause significant rainfall (scattered/fairly widespread/.widespread) over Tamil Nadu during the southwest monsoon season. It is seen that the occurrence of the synoptic systems surface trough (with or without upper air cyclonic circulation) and low pressure area- id dependent on the position of the monsoon trough with respect to the normal. There IS a high probability of occurrence of surface trough with cyclonic circulation and low pressure area when the monsoon trough is to the north of Its normal position. Also the probability of occurrence of significant rainfall is higher with low pressure area (66 %) compared to sea level trough with or without cyclonic circulation (20 %).